Effect of UV-C Irradiation and Lactic Acid Application on the Inactivation of Listeria monocytogenes and Lactic Acid Bacteria in Vacuum-Packaged Beef - Giannina Brugnini; Soledad Rodríguez; Jesica Rodríguez; Caterina Rufo (Foods, 2021)
The objective of this study was to test the effect of the combined application of lactic acid (0–5%) (LA) and UV-C light (0–330 mJ/cm2) to reduce Listeria monocytogenes and lactic acid bacteria (LAB) on beef without major meat color (L *, a *, b *) change and its impact over time. A two-factor central composite design with five central points and response surface methodology (RSM) were used to optimize LA concentration and UV-C dose using 21 meat pieces (10 g) inoculated with L. monocytogenes (LM100A1). The optimal conditions were analyzed over 8 weeks. A quadratic model was obtained that predicted the L. monocytogenes log reduction in vacuum-packed beef treated with LA and UV-C. The maximum log reduction for L. monocytogenes (1.55 ± 0.41 log CFU/g) and LAB (1.55 ± 1.15 log CFU/g) with minimal impact on meat color was achieved with 2.6% LA and 330 mJ/cm2 UV-C. These conditions impaired L. monocytogenes growth and delayed LAB growth by 2 weeks in vacuum-packed meat samples throughout 8 weeks at 4 °C. This strategy might contribute to improving the safety and shelf life of vacuum-packed beef with a low impact on meat color.